Penerapan Sectigo Positive Ssl Pada Pengamanan Web Site - Khairullah Khairullah; Evita Rahmadona; Rozali Toyib; Muhammad Imanullah (UNIVED Press, 2024)
System security is the most important aspect in an information system, weak system security increases the risk of attacks that can cause system damage. One of the attacks that often occurs is an attack on a web server, this is because the web server is connected to the internet network and is accessed by many users widely, so the risk of attack increases. For example, the New Student Admission web site of Universitas Muhammadiyah Bengkulu, which manages data on prospective new students who have registered themselves. So that a web server security system is needed to avoid potential attacks and to increase data security. One method of securing a web server is by using the Secure Socket Layer (SSL). SSL is often used to secure communication between client and server. The stages carried out in this study are scanning web servers that have not used SSL and those that have used SSL. This research aims to determine the security of web servers and anticipate various potential attacks on web servers.